A cronificação nos serviços substitutivos na rede de saúde mental de Natal/RN - Severo, Ana Kalliny de Sousa (Universidade Federal do Rio Grande do Norte, 2009)
Brazilian Psychiatry Reform, through Psychosocial Care Strategy, has intended to build insane people care practices from community care services which contemplates the subjects complete lives. However, to change the traditional care ways demands the facing of a series of epistemological, political and cultural obstacles. One of the current challenges deals with patients aggravation processes, with management ways, with devices and with professionals, as well as with the assistance network. The purpose of this thesis was to investigate how these aggravation processes has been constituted in Natal mental healthcare network, understanding its effects in the work teams and patients. Theoretical and methodological perspective used was Institutional analysis was, subsidizing the usage of concept-tools as the implication analysis, selfmanagement and self-analysis, and restitution. The research was carried out at the Natal East Sanitary District Mental Healthcare Clinic, with the participation of technicians and patients. The research procedures were: literature and document research on the attendance and the analyzed theme; attendance registers analysis; participating observation of the institutional routine for three months and field log entries; talking groups, one with the team and one with the patients. Two main discussion points are shown: 1. The mental healthcare clinic organization logic and the intersector politics; 2. The work and management processes developed at the mental healthcare clinic. The analysis show diversity in the attended demands in the service, which has favored the patients aggravation, this device and the substitute network processes. The work processes are apart from the political sphere and from the managements processes. In this sense, we show the need to reevaluate the clinic device as well as the management models adopted in the Brazilian Psychiatry Reform context
Keywords: Reforma psiquiátrica; Ambulatório; Cronificação; Trabalho; gestão; Psychiatry reform; Clinics; Cronification; Work; management; CNPQ::CIENCIAS HUMANAS::PSICOLOGIA